The New Zealand Active Faults Database. Issue 1 (2nd January 2016) - Langridge, RM; Ries, WF; Litchfield, NJ; Villamor, P; Van Dissen, RJ; Barrell, DJA; Rattenbury, MS; Heron, DW; Haubrock, S; Townsend, DB; Lee, JM; Berryman, KR; et al.
ABSTRACT: The New Zealand Active Faults Database (NZAFD) is a national geospatial database of active faults – including their locations, names and degrees of activity – that have deformed the ground surface of New Zealand within the last 125, 000 years. The NZAFD is used for geological research, hazard modelling and infrastructure planning and is an underlying dataset for other nationally significant hazard applications such as the National Seismic Hazard Model. Recent refinements to the data structure have improved the accuracy of active fault locations and characteristics. A subset of active fault information from the NZAFD, generalised for portrayal and use at a scale of 1:250, 000 (and referred to as NZAFD250), is freely available online and can be downloaded in several different formats to suit the needs of a range of users including scientists, governmental authorities and the general public. To achieve a uniform spatial scale of 1:250, 000 a simplification of detailed fault locational data was required in some areas, while in other areas new mapping was necessary to provide a consistent level of coverage. Future improvements to the NZAFD will include the incorporation of data on active folds and offshore active faults.